Notes From Texas : On Writing in the Lone Star State - Jameson, W. C., 1942- (Book collections on Project MUSE., 2008)
From the Guadalupe Mountains of the Chihuahuan Desert to the Hill Country to the Red River, the vast geographic landscape of Texas has afforded the cultural depth and diversity to inspire its writers. The richness of Texas folklore, history, and traditions has left an unmistakable mark on the art of the region. Both native and transplant Texas writers alike have been keenly shaped by the distinctive aroma of fresh corn tortillas, tales of Mescalero Apaches, and Tejano and ranchera music. Jameson has compiled an assorted collection of fourteen essays by some of the most prominent Te.